Metal contamination in Ria Formosa saltmarsh sediments and halophyte vegetation - Silva, Manuela (2019)
Saltmarsh vegetation may retain certain substances from anthropogenic activities in surrounding areas, providing a control of contaminants such as heavy metals, coming from industry, agriculture and urbanization. In the last decades there are been na increase in urbanization and industrialization of the area surrounding Marim – Ria Formosa, where this study was performed.